Origin of the Aromatic Group of Cultivated Rice (Oryza sativa L.) Traced to the Indian Subcontinent. (21st February 2019) - Civáň, Peter; Ali, Sajid; Batista-Navarro, Riza; Drosou, Konstantina; Ihejieto, Chioma; Chakraborty, Debarati; Ray, Avik; Gladieux, Pierre; Brown, Terence A
Abstract: The aromatic group of Asian cultivated rice is a distinct population with considerable genetic diversity on the Indian subcontinent and includes the popular Basmati types characterized by pleasant fragrance. Genetic and phenotypic associations with other cultivated groups are ambiguous, obscuring the origin of the aromatic population. From analysis of genome-wide diversity among over 1, 000 wild and cultivated rice accessions, we show that aromatic rice originated in the Indian subcontinent from hybridization between a local wild population and examples of domesticated japonica that had spread to the region from their own center of origin in East Asia. Most present-day aromatic accessions have inherited their cytoplasm along with 29–47% of their nuclear genome from the local Indian rice. We infer that the admixture occurred 4, 000–2, 400 years ago, soon after japonica rice reached the region. We identify aus as the original crop of the Indian subcontinent, indica and japonica as later arrivals, and aromatic a specific product of local agriculture. These results prompt a reappraisal of our understanding of the emergence and development of rice agriculture in the Indian subcontinent.